Neuroinflammatory responses to traumatic brain injury - Paiva WS (Dove Medical Press, 2015)
Wellingson Silva Paiva,1 Angelica Duarte Correia,2 Suely Kazue Marie2 1Division of Neurological Surgery, 2Laboratory of Medical Investigation 15, Department of Neurology, University of São Paulo Medical School, Sao Paulo, Brazil We read with great interest the recent study by Lozano et al1 published in the Neuropsychiatric Disease and Treatment. The recovery after traumatic brain injury (TBI) is related to severity of the initial injury (primary injury) and the presence of secondary injury.2 Evidences suggest that inflammation, oxidative stress, excitotoxicity, apoptosis, and neuroendocrine responses play an important role in the development of secondary brain injury.3 Therefore, an important part in the management of patients with TBI is trying to minimize the occurrence of deleterious secondary lesions. Lozano et al’s1 paper focused on the role of neuroinflammation in brain injury.Although some studies have described experimental drugs which may eventually have neuroprotective effects in patients with TBI,2–4 there is currently no approved pharmacological treatment for neuroinflammatory effects of the acute phase of the injury. The dissociation between experimental data with positive results and consecutive clinical trials with negative results leads to a dilemma for the treatment of patients with TBI. And, we agree with Lozano et al1 that further clarification of the neuroinflammatory mechanisms could be the basis for addressing the gap between bench and clinical results to provide better treatment and reduce death and sequelae of TBI.View original paper by Lozano and colleagues.